Phytochemistry, Mechanisms, and Preclinical Studies of Echinacea Extracts in Modulating Immune Responses to Bacterial and Viral Infections: A Comprehensive Review - Fatemeh Ahmadi (MDPI AG, 2024)
Background: Echinacea species, particularly Echinacea purpurea, Echinacea angustifolia, and Echinacea pallida, are renowned for their immunomodulatory, antibacterial, and antiviral properties. Objectives: This review explores the mechanisms by which echinacea herbal extracts modulate immune responses, focusing on their effects on both innate and adaptive immunity in bacterial and viral infections. Results: Key bioactive compounds, such as alkamides, caffeic acid derivatives, flavonoids, and polysaccharides, contribute to these effects. These compounds enhance immune cell activity, including macrophages and natural killer cells, stimulating cytokine production and phagocytosis. The antibacterial activity of echinacea against respiratory pathogens (Streptococcus pneumoniae, Haemophilus influenzae, Legionella pneumophila) and skin pathogens (Staphylococcus aureus, Propionibacterium acnes) is reviewed, as well as its antiviral efficacy against viruses like herpes simplex, influenza, and rhinovirus. Echinacea's potential as a complementary treatment alongside conventional antibiotics and antivirals is discussed, particularly in the context of antibiotic resistance and emerging viral threats. Conclusions: Challenges associated with variability in phytochemical content and the need for standardized extraction processes are also addressed. This review provides a comprehensive overview of echinacea's therapeutic potential and outlines future directions for research, including clinical trials and dosage optimization.